Adenovirus DNA replication in vitro: identification of a host factor that stimulates synthesis of the preterminal protein-dCMP complex. - Nagata, K (1982)
A protein factor that participates in the formation of a covalent complex between the 80,000-dalton precursor of the adenovirus (Ad) terminal protein (pTP) and 5'-dCMP has been isolated and characterized. This 47,000-dalton protein, isolated from nuclear extracts of uninfected HeLa cells, has been designated nuclear factor I. It is free of detectable DNA polymerase alpha, beta, and gamma activities. In the presence of Ad DNA-prot, the Ad-protein fraction (containing the pTP and the Ad-associated DNA polymerase), ATP, Mg2+, and dCTP, nuclear factor I stimulates formation of the pTP-dCMP complex. Addition of the Ad DNA binding protein (Ad DBP) renders the formation of the pTP-dCMP complex completely dependent on the addition of nuclear factor I. When Ad DNA-prot is replaced with phi X174 single-stranded circular DNA, pTP-dCMP complex formation requires only the Ad-protein fraction; Ad DBP and ATP are inhibitory and nuclear factor I has no effect on this reaction. This suggests that the initiation reaction observed with Ad DNA-prot in the absence of Ad DBP occurs at single-stranded DNA sites. In the presence of Ad DBP, these sites are blocked thus creating a requirement for nuclear factor I in pTP-dCMP complex formation.